Anhydrous proton conductivity of electrospun phosphoric acid-doped PVP-PVDF nanofibers and composite membranes containing MOF fillers. Issue 47 (2nd September 2021) - Sun, Lian; Gu, Quanchao; Wang, Honglei; Yu, Jinshan; Zhou, Xingui
Abstract : A composite SA/MIL101@PVP-PVDF membrane was fabricated via electrospinning and reached a conductivity of 0.237 S cm −1 at 160 °C with a moderate acid doping level (12.7). Abstract : A high-temperature proton exchange membrane was fabricated based on polyvinylidene fluoride (PVDF) and polyvinylpyrrolidone (PVP) blend polymer nanofibers. Using electrospinning method, abundant small ionic clusters can be formed and agglomerated on membrane surface, which would facilitate the proton conductivity. To further enhance the conductivity, phosphoric acid (PA) retention as well as mechanical strength, sulfamic acid (SA)-doped metal–organic framework MIL-101 was incorporated into PVP-PVDF blend nanofiber membranes. As a result, the anhydrous proton conductivity of the composite SA/MIL101@PVP-PVDF membrane reached 0.237 S cm −1 at 160 °C at a moderate acid doping level (ADL) of 12.7. The construction of long-range conducting network by electrospinning method combined with hot-pressing and the synergistic effect between PVP-PVDF, SA/MIL-101 and PA all contribute to the proton conducting behaviors of this composite membrane.